Culturally responsive early childhood education: teachers’ perspectives and practices on local culture in Indonesia - Rohita; Yetti, Elindra; Sumadi, Tjipto (Proceedings of International Conference on Research in Education, 2025)
In response to cultural homogenization driven by globalization, integrating local culture into early childhood education (ECE) supports culturally responsive pedagogy. This study explores how ECE teachers in Indonesia perceive and apply local culture in curriculum and lesson planning. Using a cross-sectional survey of 74 teachers in Lebak Regency, Banten, the study analyzed cultural awareness, planning behavior, and teaching strategies. Results show that teachers value local traditions and incorporate food, clothing, games, housing, and folklore into classroom activities using project-based learning, field trips, and discussions. These are commonly integrated into thematic units like “My Environment” and “My Country.” However, only 30.41% of teachers formally document cultural elements in lesson plans, indicating a gap between practice and written curriculum. This gap may hinder the formal preservation of intangible heritage. The study highlights the need for institutional support and professional development to strengthen the alignment between teaching practices and curriculum documentation.